Differential ecological traits of two Phlebotomus sergenti mitochondrial lineages in southwestern Europe and their epidemiological implications. Issue 5 (17th March 2016) - Merino‐Espinosa, G.; Corpas‐López, V.; Callejón‐Fernández, R.; Porcel‐Rodríguez, L.; Díaz‐Sáez, V.; Gállego, M.; Ballart, C.; Molina, R.; Jiménez, M.; Morillas‐Márquez, F.; Martín‐Sánchez, J.
Abstract: Objectives: The introduction of leishmaniasis in a new area requires a well‐established population of the sandfly vector species of the parasite. No autochthonous cases of anthroponotic cutaneous leishmaniasis have been detected in southwestern Europe, and Leishmania infantum is the only causative agent of leishmaniasis in this area. Phlebotomus sergenti, the main vector of Leishmania tropica, is commonly found in the Iberian Peninsula at sufficient densities to be able to act as a vector. It is characterised by high genetic diversity and classified in four mitochondrial lineages. Our aim was to analyse the composition and distribution of P. sergenti mitochondrial lineages in southwestern Europe given the possibility of phenotypic differences of biomedical importance between them. Methods: Sandflies were captured in the Iberian Peninsula and on the Canary and Balearic Islands. Mitochondrial lineage identification of 137 P. sergenti was performed using a novel PCR‐RFLP that avoids the necessity of gene sequencing. Results: Two lineages were evidenced, the typical Iberian one (lineage I) and another, held in common with North Africa (lineage III), that show a distinctive distribution. P. sergenti lineage I shows a better correlation to the bioclimatic diversity in southwestern Europe. Conversely, P. sergenti lineage III prefers warmer temperatures and less precipitation, which are typical of the Mediterranean. Conclusion: Lineage I seems to have adaptive advantages given its wider tolerance to temperature and altitude than lineage III, and it would seem more suitable to lead a potential geographical expansion towards the rest of Europe.